Pengembangan Bahan Ajar Digital Berbasis Pedagogi Kritis pada Materi Peninggalan Sejarah dari Masa Hindu, Budha, dan Islam di Indonesia - Alfarizkhi Intan Maharani; Almuntaqo Zainuddin (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
Social studies education is one of the compulsory subjects in elementary schools, but social studies lessons are still considered as second grade lessons. In addition, social studies lessons emphasize more on aspects of knowledge, facts, and concepts that are rote so that students are not involved intellectually or emotionally in dealing with social problems around them. Based on the problems above, an alternative that can be used to solve social studies learning problems so as to improve students' critical thinking skills and involve students in playing an active role in their social environment is to change the learning approach towards critical pedagogy. The purpose of this research is to provide knowledge to students about social problems that exist in society regarding the existence of injustice or oppression, especially those related to Historical Heritage material from the Hindu, Buddhist, and Islamic Periods in Indonesia, namely about caste in grade IV elementary school. The method used in this research is R&D (Research and Development) research using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques in this study were in the form of observation, interviews, questionnaires, and documentation. The validation test in this study was in the form of an assessment questionnaire on two expert lecturers, namely media and material experts. The results of the validation test after testing the media experts get a score of 54 and the material experts get a score of 50. If it is expressed in percentage form, the results on the media validation test get 83% and the material validation test gets 76% and if it is expressed in qualitative form then the teaching materials was declared very feasible.